Efisiensi Teknis Produk Olahan Kulit Manggis Sebagai Pakan Ternak pada Peternakan Desa Cihateup Kabupaten Tasikmalaya - Jakiyah, Ulpah; Umbara, Dona Setia (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Mangosteen farmers in Tasikmalaya Regency experience marketing difficulties when harvesting mangosteen. So it is necessary to use mangosteen as a raw material for products. The development of processed mangosteen peel products that have been carried out includes food ingredients, beverage ingredients, and health. This is due to the high levels of antioxidants which are good for health. Farmers and researchers in Tasikmalaya Regency process mangosteen peel as antioxidant animal feed. However, feed production activities have not been carried out commercially because we do not yet know the level of efficiency and added value of feed. So this research aims to determine the level of efficiency. The research method used was carried out using two approaches, namely observational and quantitative tests. Descriptive analysis is to measure the effectiveness of mangosteen peel antioxidants as animal feed. Qualitative analysis uses a survey approach with sampling using started random sampling. The number of samples in this study was 20 breeders. The analysis tool used is the Stochastic Frontier. The results of this research indicate that the production of processed mangosteen peel products as duck feed is inefficient. However, several things must be considered, including giving concentrate and giving mangosteen peel powder. Apart from that, there is more intensive handling carried out by Cihateup duck breeders to increase the quality and quantity of eggs.